2015
DOI: 10.1021/acs.cgd.5b01188
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Solid-State Phase Transitions of dl-Norleucine: An in Situ DSC, Microscopy, and Solid-State NMR Study

Abstract: The solid-state phase transitions between the α, β and γ forms of DL-norleucine were studied using DSC, thermal stage polarization microscopy and solid-state NMR. Since the crystals consist of 2D hydrogen-bonded bilayers with van der Waals interactions between consecutive bilayers, the transitions occur in a layer-wise fashion with a propagating transformation front. The α↔γ transition at 390 K is a clear example of a first order transition with a relatively large enthalpy difference between the polymorphs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 46 publications
5
52
0
Order By: Relevance
“…The DSC measurement revealed two sharp endothermic peaks at T c = 260.56 and 260.49 K on the first and second heatings, respectively, and a sharp exothermic peak at 255.89 K on cooling (Fig. 2), which indicated a reversible first-order transition similar to other reported phase transitions (Chen et al, 2015;Khan et al, 2015;Smets et al, 2015;Takanabe et al, 2017;Zeb et al, 2017). The observed enthalpy change and heat hysteresis are 4.34 J g À1 and 4.64 K. The average entropy change, ÁS, measured from the DSC curve is 0.0168 J g À1 K À1 or 6.4584 J mol À1 K À1 , and provided ÁS ¼ R ln N, then the possible configurations, N, equals to 2.17, indicating the two-site order-disorder characteristic of the studied transition (Asghar et al, 2016;Besara et al, 2011;Jain et al, 2009;Mą czka et al, 2014).…”
Section: Structural Phase Transition Of Hbasupporting
confidence: 81%
“…The DSC measurement revealed two sharp endothermic peaks at T c = 260.56 and 260.49 K on the first and second heatings, respectively, and a sharp exothermic peak at 255.89 K on cooling (Fig. 2), which indicated a reversible first-order transition similar to other reported phase transitions (Chen et al, 2015;Khan et al, 2015;Smets et al, 2015;Takanabe et al, 2017;Zeb et al, 2017). The observed enthalpy change and heat hysteresis are 4.34 J g À1 and 4.64 K. The average entropy change, ÁS, measured from the DSC curve is 0.0168 J g À1 K À1 or 6.4584 J mol À1 K À1 , and provided ÁS ¼ R ln N, then the possible configurations, N, equals to 2.17, indicating the two-site order-disorder characteristic of the studied transition (Asghar et al, 2016;Besara et al, 2011;Jain et al, 2009;Mą czka et al, 2014).…”
Section: Structural Phase Transition Of Hbasupporting
confidence: 81%
“…This small number might explain why experimentally part of the crystal is found not to transform over the course of several hours. 21 For these cases, the onset of a possible transition might require more than 180 molecules to move concertedly. One could imagine that the amount of molecules required is dictated by the local defect density.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with experimental thermal stage microscopic observation where in some cases the crystal is found to "wobble" during the transition, but the cell parameters before and after the transition are again the same. 14,21 The dashed line in Fig. 5 shows the fit with only the prefactor as a free parameter and .…”
Section: Nudged Elastic Band Calculationsmentioning
confidence: 99%
“…Being cognizant that the restricted C−C bond rotations would limit the formation of a 6‐membered planar ring (between the exchanging atomic centers), the occurrence of an intramolecular proton exchange in the solid state of PDA⋅H 2 O would be improbable. As such, temperature‐dependent SCXRD experiments were carried out to study the dynamicity of the solution mediated proton transfer in triggering possible solid‐state phase transitions . Through detailed temperature dependent SCXRD studies and DSC measurements, it was revealed that a reversible phase transition (Figure ) occurred, from the monoclinic system ( C 2/ c ) at 298 K to the triclinic one (()P1 ), at 168 K (Figure : Table S2); this phenomenon was distinct from the unchanged (P2 1 2 1 2 1 ), orthorhombic system, which was observed for dipic monohydrate …”
Section: Resultsmentioning
confidence: 99%